Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa dengan Materi Ekositem Kelas X SMA - Mansur S; Paulina Nelce Mole (Peneliti.net, 2021)
This study aims to increase the motivation and learning outcomes of class X students of SMA Negeri 2 Maumere through the application of the STAD type cooperative learning model with ecosystem materials. This research is a classroom action research (CAR) with two cycles of action consisting of action planning, action implementation, observation, and reflection. The subjects of this study were students of class X IPA I SMA Negeri 2 Maumere with a total of 36 students. Data collection methods include students' learning motivation in STAD type cooperative learning and test result data which is carried out at the end of each cycle. Data analysis was carried out in a quantitative descriptive manner. The results showed that students' learning motivation increased by giving a questionnaire in the first cycle with a total of 36 students who had attitudes or interests with a sufficient category of 10 people, good 8 people, very good 2 people and less 16 people, while in the second cycle there was an increase with the number of students who have attitudes or interests with categories, enough 5 people, less 2 people, good 25 people, very good 4 people. Learning outcomes showed an increase in the percentage of students who completed classical learning, increased from 69.44% in the first cycle, an increase of 100% in the second cycle. The increase in the value of students' learning motivation in each cycle shows that the STAD type cooperative learning model can increase the motivation and learning outcomes of students in class X IPA I SMA Negeri 2 Maumere.